2023
DOI: 10.1177/14604582231154478
|View full text |Cite
|
Sign up to set email alerts
|

The association between information technology sophistication and patient portal use: A cross sectional study in Eastern North Carolina

Abstract: Even with the extolled benefits of patient portals, there has been some challenges to ensuring patient portal use. This study examines if a patient’s level of information technology (IT) sophistication, defined as the degree of use of diverse information technologies by an individual, is associated with their use of a patient portal. Patients previous experience and exposure to other similar technologies like desktop computer, laptop, internet, smart phone, or social media explains their willingness to use inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies have found that patients use portals if they perceive them to offer a relative advantage over existing practices such as calling or traveling for an inpatient visit with their provider [44]. Given that patients with multimorbidity tend to have complex health needs, rely on a network of providers, and consume more medical services than those without chronic diseases [45][46][47], theory suggests that they would be able to recognize the benefits and anticipated advantages that portal messaging could offer [48,49]. However, it is possible that such advantages are not yet fully realized by older patients or that they may focus more on the portal's incompatibility with their values or experiences.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Studies have found that patients use portals if they perceive them to offer a relative advantage over existing practices such as calling or traveling for an inpatient visit with their provider [44]. Given that patients with multimorbidity tend to have complex health needs, rely on a network of providers, and consume more medical services than those without chronic diseases [45][46][47], theory suggests that they would be able to recognize the benefits and anticipated advantages that portal messaging could offer [48,49]. However, it is possible that such advantages are not yet fully realized by older patients or that they may focus more on the portal's incompatibility with their values or experiences.…”
Section: Principal Findingsmentioning
confidence: 99%
“…ICTs today are used in different fields that allow the processing, management, storage, care and sharing of information from different technological resources, for example, it has brought many benefits in the area of health [3] [4], since, during the coronavirus pandemic (COVID-19), the digitization of health records, care remotely, and the processing of surveys executed by health workers virtually and that this has allowed the decrease in the contagion by COVID-19 of the workers who perform these tasks [5] [6].…”
Section: Introductionmentioning
confidence: 99%